Nuclear Targeting of Gold Nanoparticles for Improved Therapeutics - J. Yang, Celina; B. Chithrani, Devika (Current Topics in Medicinal Chemistry, 2016)
Nanomedicine is an exponentially growing field, and gold nanoparticles (GNPs) in particular are extensively used in research due to their abilities as anti-cancer drug carriers for chemotherapy and as dose enhancers in radiotherapy. Most GNP research in the past involved a system where GNP localization was in the cytoplasm of the cell. However, it is predicted that therapy response can be enhanced if GNPs can be effectively targeted into the nucleus. With nuclear targeting, there is a possibility in producing additional free radicals in response to irradiation within the nucleus. This can cause more damage to the DNA of cancer cells. In this review article, we discuss the successful NP-based platforms available for nuclear targeting. In addition, we also present the possible mechanisms of nuclear targeting in detail followed by its applications in cancer therapy.
Keywords: Cancer research